Strategi Pemasaran UMKM: Studi Pada Umkm Tuwu Mori Kota Bima - Dwi Tesna Andini; Selva Selva (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The objective of this research is to identify marketing strategies that align with the strengths and weaknesses of SMEs (Tuwu Mori) in view of existing opportunities and threats. This research employs an exploratory research design. The research is conducted at Tuwu Mori SMEs in Bima City. Data analysis in this research involves three simultaneous activities: (1) data condensation; (2) data display; and (3) drawing conclusions/verification. The research results indicate that the main strengths of Tuwu Mori SMEs lie in unique, high-quality, and child-friendly products, as well as product variety. Meanwhile, the main weaknesses include suboptimal distribution channels, low utilization of online marketplaces, minimal business management capabilities, and unclear business identity. Key opportunity factors include government stimuli, ease of access to online business, and an open market share. On the other hand, the main threats hindering progress are numerous competitors and rapidly changing market preferences. The process of matching the strengths and weaknesses of the company with opportunities and threats leads to the creation of four recommended strategies: integration, branding, enhanced managerial capabilities, and optimization of digital marketing.